Perancangan Instrumen Go-Green Movement Inventory dalam Konteks Gerakan Go-Green - Sulisma Meliati; Afandi Afandi; Eko Sri Wahyuni (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The purpose of this research was to examine the content validity, inter-rater reliability, item validity, and item reliability of the Go-Green Movement Inventory (GGMI) instrument developed for high school students. The instrument development process utilized the Research & Development (R&D) method by Borg and Gall in Sugiyono (2019), up to the fourth stage. Prior to testing the instrument with 148 high school students, validation was conducted by 5 experts comprising two university lecturers and three high school teachers. The research findings indicate that the content validity analysis of the Go-Green Movement Inventory (GGMI) instrument for high school students is valid, as evidenced by Vhitung > Vtabel, specifically 0.89 > 0.87. Inter-rater reliability analysis yielded a score of 0.79, categorized as moderate. Item validity analysis revealed that out of 30 statement items, 2 items were rejected: item number 13 and 30, while the rest were accepted. Item reliability analysis showed a person reliability value of 0.80, indicating good consistency in student responses, and an item reliability of 0.96, indicating excellent quality of individual items. The Cronbach's Alpha coefficient was 0.83, indicating good overall interaction between respondents and item statements.